Other Kinds of Soft Î² maps via Soft Topological Ordered Spaces (European Journal of Pure and Applied Mathematics, 2019)
The authors of [13] formulated a soft topological ordered spaces concept and then they established and studied some ordered mappings [14]. In the present work, we define new ordered mappings via soft topological ordered spaces based on soft Î²-open sets, namely soft xÎ²-continuous, soft xÎ²-open, soft xÎ²-closed and soft xÎ²-homeomorphism mappings, for x âˆˆ {I, D, B}. We give various characterizations of each one of the introduced soft mappings. One of the most important obtained results is that an extended soft topologies notion guarantees the equivalentÂ  between the soft mappings initiated herein and their counterparts of mappings on topological ordered spaces. We provide several interesting examples to examine the relationships among these soft mappings.